Phase transitions for the geodesic flow of a rank one surface with nonpositive curvature. Issue 3 (3rd July 2021) - Burns, K.; Buzzi, J.; Fisher, T.; Sawyer, N.
Abstract : We study the one parameter family of potential functions q φ u associated with the unstable Jacobian potential (or geometric potential) φ u for the geodesic flow of a compact rank 1 surface of nonpositive curvature. For q <1, it is known that there is a unique equilibrium state associated with q φ u, and it has full support. For q >1 it is known that an invariant measure is an equilibrium state if and only if it is supported on the singular set. We study the critical value q = 1 and show that the ergodic equilibrium states are either the restriction to the regular set of the Liouville measure or measures supported on the singular set. In particular, when q = 1, there is a unique ergodic equilibrium state that gives positive measure to the regular set.